9-cis-Retinoic Acid Improves Disease Modelling in iPSC-Derived Liver Organoids - Mina Kazemzadeh Dastjerd; Vincent Merens; Ayla Smout; Rebeca De Wolf; Christophe Chesné; Catherine Verfaillie; Stefaan Verhulst; Leo A. van Grunsven (Cells)
Liver fibrosis majorly impacts global health, necessitating the development of in vitro models to study disease mechanisms and develop drug therapies. Relevant models should at least include hepatocytes and hepatic stellate cells (HSCs) and ideally use three-dimensional cultures to mimic in vivo conditions. Induced pluripotent stem cells (iPSCs) allow for patient-specific liver modelling, but current models based on iPSC-derived hepatocytes (iHepatocytes) and HSCs (iHSCs) still lack key functions. We developed organoids of iHepatocytes and iHSCs and compared them to HepaRG and primary HSC organoids. RNA sequencing analysis comparison of these cultures identified a potential role for the transcription factor RXRA in hepatocyte differentiation and HSC quiescence. Treating cells with the RXRA ligand 9-cis-retinoic acid (9CRA) promoted iHepatocyte metabolism and iHSC quiescence. In organoids, 9CRA enhanced fibrotic response to TGF-β and acetaminophen, highlighting its potential for refining iPSC-based liver fibrosis models to more faithfully replicate human drug-induced liver injury and fibrotic conditions.